Artificial intelligence (AI) competencies for organizational performance : A B2B marketing capabilities perspective - Mikalef, Patrick; Islam, Najmul; Parida, Vinit; Singh, Harkamaljit; Altwaijry, Najwa (Elsevier, 2023)
The deployment of Artificial Intelligence (AI) has been accelerating in several fields over the past few years, with much focus placed on its potential in Business-to-Business (B2B) marketing. Early reports highlight promising benefits of AI in B2B marketing such as offering important insights into customer behaviors, identifying critical market insight, and streamlining operational inefficiencies. Nevertheless, there is a lack of understanding concerning how organizations should structure their AI competencies for B2B marketing, and how these ultimately influence organizational performance. Drawing on AI competencies and B2B marketing literature, this study develops a conceptual research model that explores the effect that AI competencies have on B2B marketing capabilities, and in turn on organizational performance. The proposed research model is tested using 155 survey responses from European companies and analyzed using partial least squares structural equation modeling. The results highlight the mechanisms through which AI competencies influence B2B marketing capabilities, as well as how the later impact organizational performance.
Keywords: Artificial intelligence; B2B marketing; AI competencies; Core competencies theory; fi=Strateginen johtaminen|en=Strategic Management|